2006
DOI: 10.1007/s11030-006-7009-0
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids on the rampant primordial Earth: Electric discharges and the hot salty ocean

Abstract: For more than 50 years scientists who study prebiotic chemistry have been dealing with chemical evolution as it could have possibly taken place on the primordial Earth. Since we will never know what processes have really taken place around 3.8 to 4 billion years ago we can only come up with plausible reaction pathways that work well in an early Earth scenario as indicated by geochemists. In our work we have investigated the plausibility of one particularly important branch of prebiotic chemistry, the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Low-efficiency syntheses of amino acids have been reported under neutral atmospheric conditions (Abelson 1966;Folsome et al 1981;Schlesinger and Miller 1983;Plankensteiner et al 2006). The results presented here extend previous reports and demonstrate that neutral atmospheres can provide biochemical monomers in much higher yield than previously thought.…”
Section: Discussionsupporting
confidence: 86%
“…Low-efficiency syntheses of amino acids have been reported under neutral atmospheric conditions (Abelson 1966;Folsome et al 1981;Schlesinger and Miller 1983;Plankensteiner et al 2006). The results presented here extend previous reports and demonstrate that neutral atmospheres can provide biochemical monomers in much higher yield than previously thought.…”
Section: Discussionsupporting
confidence: 86%
“…Miller (1953) was the first who showed that the synthesis of amino acids was possible from a mixture of gases. Table 5 shows several protein amino acids as well as non-protein amino acids that were synthesized in environments simulating the atmosphere of prebiotic earth (Janda et al 2008;Ruiz-Bermejo et al 2007;Plankensteiner et al 2006;Civiš et al 2004;Miyakawa et al 2002;Kobayashi et al 2001;Kobayashi et al 1999b;Miyakawa et al 1999;Takahashi et al 1999;Kobayashi et al 1998;Hirose et al 1990Hirose et al -1991Kobayashi et al 1990;Schlesinger and Miller 1983;Shimoyama et al 1978;Becker et al 1974;Sagan and Khare 1971;Bar-Nun et al 1970;Miller 1953).…”
Section: Sources Of Amino Acids On the Prebiotic Earthmentioning
confidence: 99%
“…Most of the amino acids shown in Table 5 have also been found in ISM simulation experiments (Table 1) and in meteorites (Tables 2, 3, 4). However, there are two amino acids (α-lysine-traces, α-histidine-traces) synthesized by Plankensteiner et al (2006) (redox-neutral atmospheres), one (α-histidine-trace) synthesized by Ruiz-Bermejo et al (2007) and one (α-asparagine) synthesized by Civiš et al (2004) (redox-neutral atmospheres) that were not synthesized in ISM experiments (Table 1) or found in meteorites (Tables 2, 3, 4). Nuevo et al (2008) were not able to confirm the synthesis of α-histidine and α-lysine in ISM experiments.…”
Section: Endogenous Amino Acidsmentioning
confidence: 99%
“…Only a few works describe the effect of saline solutions in this type of experiment (Plankensteiner et al 2006;Manolache et al 1997;Kobayashi et al 1990). Nonetheless, it has been postulated that the ancient sea had a salinity of the 1.5 to 2 times the modern value (Knauth 2005; Morse and Mackenzie 1998) and a pH=4-10, although the pH value of early ocean water is under debate (see Kempe and Kazmierczak 2002;Morse and Mackenzie 1998;Russell and Hall 1997;Williams and Frausto da Silva 1996;Bada et al 1994;Macleod et al 1994;Grotzinger and Kasting 1993;Kasting 1993;Gregor et al 1988;Holland et al 1986;Walker 1985).…”
Section: Introductionmentioning
confidence: 99%